Back Cover: Numeric Optimization for Configurable, Parallel, Error‐Robust Entangling Gates in Large Ion Registers (Adv. Quantum Technol. 11/2020). Issue 11 (6th November 2020) - Bentley, Christopher D. B.; Ball, Harrison; Biercuk, Michael J.; Carvalho, Andre R. R.; Hush, Michael R.; Slatyer, Harry J.
Abstract : Novel optimization tools now enable high‐efficiency parallel entangling gates within a register of trapped‐ions. Using quantum control it becomes possible to simultaneously target arbitrary groups of ions for execution of entangling operations while others remain unaffected, while also adding error‐robustness against trap instabilities. By framing the problem of obtaining target quantum gates using complex drives, and exploiting computationally efficient numeric optimization, Michael J. Biercuk and co‐workers obtain flexible, reconfigurable, and approximately time‐optimal control solutions (see article number 2000044 ).